Paying people for getting vaccinated?: a favorable solution for both vaccine-hesitant persons and the public - Reese, Alexander (Bioethics, 2022)
Coase theorem, COVID‐19, pandemic ethics, vaccination ethics, vaccination hesitancy, vaccination payment